Vacant Land Tax and Land Use under Uncertainty - Preechametta, Arayah (Journal of Applied Economics and Management Strategy, 2023)
This paper presents an analytical framework for solving dynamic land use problems under uncertainty. Landowners must choose both the optimal development time and the optimal type of land use, simultaneously, given future uncertainty. They will have to pay high land utilization adjustment cost if they make wrong decision. Therefore, landowners may need to keep some vacant lands as their options until sufficient information become available. Imposing high vacant land tax on landowner, as suggested by the approach of a static analysis, may likely fail to reduce the amount of vacant land as targeted.